An investigation of decisions that drive socially responsible investment - Nybom, Jozefine (2012)
This research investigates the priorities that have the most the significant influence on the decision-making process for potential investors considering socially responsible investments (SRI). It was found that the individual financial advisor (IFA) has a great impact on an individual investor’s decision-making process, especially today with increased attention towards climate change. Four IFAs from different consultancies in UK were interviewed to understand what happens in the meeting with a client. Results show that the IFA can influence the clients’ choice of funds. It is also evident that clients choosing SRI funds often have a higher level of education. In general socially responsible investors (SRIs) are less willing to trade funds in their existing portfolio due to limited diversity amongst existing funds available. As a result, there is an increasing demand for Environment, Social and Governance (ESG) criteria to be implemented in the screening process; however, this is still in progress. When looking further into the screening process it is reasonable to question whether SRI is an investment for “doing good” or more accurate to be classified simply as a “brand” or “trademark”.